Medical metal surface piezoelectric coating and preparation method thereof

Through laser ablation and hydrothermal reaction, the problems of poor bonding force and low mechanical strength of the implant in the bone and piezoelectric coating are solved, and the piezoelectric coating is uniformly and firmly attached to the metal surface is achieved, which improves the biocompatibility and mechanical properties of the implant.

CN119530796AActive Publication Date: 2025-02-28SHANDONG FIRST MEDICAL UNIV & SHANDONG ACADEMY OF MEDICAL SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411503231.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The problems of poor bonding strength and low mechanical strength of existing implants in bone and piezoelectric coatings affect their practical application in the medical field.

Method used

The metal surface is ablated by laser surface direct writing technology to form an oxidized nanocoat, and then hydrothermal reaction is carried out under high temperature and high pressure conditions to synthesize the piezoelectric coating. This method not only improves the mechanical strength of the metal surface, but also ensures uniformity and adhesion of the piezoelectric coating.

Benefits of technology

The piezoelectric coating is uniformly and firmly attached to the metal surface, which improves the biocompatibility and mechanical properties of the implant and enhances its effect in osseous integration and antibacterial.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530796A_ABST
    Figure CN119530796A_ABST
Patent Text Reader

Abstract

The invention discloses a medical metal surface piezoelectric coating and a preparation method thereof, and belongs to the technical field of medical biomaterial implants, the preparation method of the piezoelectric coating comprises the following steps: carrying out surface laser ablation on metal to obtain an oxidized nano coating; carrying out hydrothermal reaction on an alkaline solution and the oxidized nano coating under high-temperature and high-pressure conditions to obtain a piezoelectric coating; wherein the metal is tantalum, titanium or niobium; the conditions of high temperature and high pressure are 100-300 DEG C and 1-30 MPa. The problems that an existing implant bone and a piezoelectric coating are poor in binding force, low in mechanical strength, poor in biocompatibility and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical biomaterial implants, and in particular relates to a medical metal surface piezoelectric coating and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In the medical field, implant-related infection remains a challenging clinical problem, and traditional treatments rely on the use of antibiotics or physical surgery to remove implants and infected tissues. How to effectively improve the osteogenic properties and antibacterial ability of implants has become a research hotspot. Although traditional orthopedic implants such as titanium alloys, ceramics, and polymer materials have good mechanical properties and biocompatibility, they have the risk of bacterial infection during the bone integration process, which not only affects the function of the implant, but may also lead to serious complications such as osteomyelitis and implant failure.

[0004] In clinical practice, some exogenous physical inducers have been greatly developed and applied. Piezodynamic therapy (SDT) has attracted extensive attention in antibacterial therapy due to its unique therapeutic advantages such as non-invasiveness, flexibility, repeatability and controllability. The mechanism of SDT is that the sonosensitizer absorbs ultrasound (US) energy, triggering the separation of electron-hole pairs, which leads to redox reactions and the generation of reactive oxygen species. Reactive oxygen species exert a strong antibacterial effect by causing bacterial lipid peroxidation, biofilm destruction, and ultimately bacterial death.

[0005] Piezoelectric materials have the property of generating electric charges when subjected to mechanical stress, which can stimulate the growth and differentiation of bone cells. The osteogenesis mechanism of piezoelectric coatings mainly relies on the electric field formed by the coating around the bone cells, which can mimic the electrical signals in natural bone tissue, activate the biological programs of osteoblasts (such as osteoblasts and mesenchymal stem cells), and then promote the formation of new bone.

[0006] At present, the most effective piezoelectric catalytic materials are inorganic metal oxides or sulfides, including BaTiO3, SrTiO3, LiTaO3, KNbO3 and MoS2. Studies have shown that the use of ultrasound-triggered piezoelectric materials can effectively treat bacterial-induced osteomyelitis. Therefore, piezoelectric materials have broad application prospects in the treatment of peri-implantitis and implant-induced osteomyelitis.

[0007] However, although piezoelectric coating technology has shown great potential in research, it still faces many challenges in practical applications. For example, most bio-related applications of piezoelectric materials are usually in the form of nanoparticles, which may involve invasiveness, and nanoparticles are easily cleared and excreted by the body, and their limited scope of use hinders their practical application in dentistry. How to ensure the stability and durability of the coating on the implant surface, and how to optimize the piezoelectric properties of the coating to meet the needs of different types of bone injuries are all problems that need to be solved. At the same time, the existing technical means of preparing piezoelectric coatings on the implant surface not only have problems such as weak adhesion and poor uniformity, but also use mechanical cutting, the material is easily deformed or damaged, affecting the accuracy of the implant. Summary of the invention

[0008] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a medical metal surface piezoelectric coating and a preparation method thereof, so as to solve the problems of poor bonding between the existing implant bone and the piezoelectric coating, low mechanical strength, etc.

[0009] In order to achieve the above object, the first aspect of the present invention discloses a method for preparing a medical metal surface piezoelectric coating, comprising:

[0010] Surface laser ablation of metals to obtain oxidized nano-coatings;

[0011] The alkaline solution and the oxidized nano-coating are subjected to a hydrothermal reaction under high temperature and high pressure conditions to obtain a piezoelectric coating;

[0012] Wherein, the metal is tantalum, titanium or niobium; the high temperature and high pressure conditions are 100-300°C and 1-5MPa.

[0013] In some embodiments, the metal is pretreated before laser ablation; preferably, the metal is polished with sandpaper, then cleaned with an organic solvent and pure water in sequence, and finally dried at 20-40°C; further preferably, the medical metal is polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 minutes in sequence, and dried at 25-35°C for 12-24 hours.

[0014] In some embodiments, laser ablation is performed in air.

[0015] In some embodiments, the laser ablation is laser surface direct writing ablation; preferably, it is performed using a pulsed laser; further preferably, the wavelength of the pulsed laser is 532-1064nm, the pulse width is 0.5-15ns, and the power density is 0.5-15.0J / cm 2 , frequency is 50-500Hz.

[0016] In some embodiments, the metal after laser ablation is cleaned and dried before undergoing a hydrothermal reaction; preferably, the metal after laser ablation is cleaned and dried, and the preferred method is: rinse with pure water and anhydrous ethanol respectively and ultrasonicate for 10-30 minutes, and finally dry at 30-50°C for 12-24 hours.

[0017] In some embodiments, the alkaline solution is one or both of strontium hydroxide and strontium carbonate; preferably, it is a mixed solution of strontium hydroxide and strontium carbonate. Further preferably, the concentration of strontium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of strontium carbonate is 0.01-1 mol / L.

[0018] In some embodiments, the alkaline solution is one or both of barium hydroxide and barium carbonate; preferably, it is a mixed solution of barium hydroxide and barium carbonate. Further preferably, the concentration of barium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of barium carbonate is 0.01-1 mol / L.

[0019] In some embodiments, the alkaline solution is one or both of lithium hydroxide and lithium carbonate; preferably, it is a mixed solution of lithium hydroxide and lithium carbonate. Further preferably, the concentration of lithium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of lithium carbonate is 0.01-1 mol / L.

[0020] In some embodiments, after the hydrothermal reaction, the metal is cleaned and dried; a preferred method is to wash with pure water and anhydrous ethanol respectively and ultrasonicate for 10-20 minutes, and finally dry at 30-50° C. for 12-24 hours.

[0021] The second aspect of the present invention discloses a medical metal surface piezoelectric coating, which is obtained by the above-mentioned preparation method.

[0022] In some embodiments, the particle size of the piezoelectric coating on the metal surface is 10-100 nm.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention utilizes a hydrothermal synthesis method to in-situ grow a layer of piezoelectric particles on the metal surface after laser ablation, thereby obtaining a uniform and highly adherent piezoelectric nano coating on the metal surface. By laser ablation of the metal, laser ablation is used instead of mechanical cutting, which can not only prevent material deformation or damage and improve the accuracy of the metal implant, but also quickly obtain complex and precise surface geometry. The metal surface after laser ablation has a strong mechanical strength. A metal oxide nano coating is formed on the metal surface after laser ablation, so that a hydrothermal reaction can be carried out later. The hydrothermal reaction is carried out using an alkaline solution, and the reaction energy consumption is low, the conditions are mild, and the synthesized material has a high purity. The present invention can control the crystal morphology and particle size of the final piezoelectric coating by adjusting the temperature, time, solution pH value, etc., and is suitable for the preparation of various forms of nanostructures (such as nanowires, nanorods, and nanosheets, etc.).

[0025] 2. The use of laser surface direct writing technology can achieve nanometer-level processing accuracy, which is very suitable for micro-nano processing that requires fine structures. This process can generate complex and precise surface geometries with high resolution in a clean and fast manner, which is superior to other surface modification technologies. At the same time, compared with machined surface implants, laser surface direct writing technology implants induce significantly more bone-implant contact. Laser processing is non-contact and does not apply mechanical pressure to the material, avoiding material deformation or damage that may be caused by traditional mechanical processing. In addition, laser processing is fast, especially suitable for large-area and high-repeatability micro-nano structure processing, which improves production efficiency. Moreover, the metal surface after laser ablation has strong mechanical strength, which lays the foundation for the preparation of uniform and firm piezoelectric coatings.

[0026] 3. The piezoelectric coating is prepared by hydrothermal synthesis. Water allows the reactants to be fully dissolved and mixed, reducing the introduction of impurities, so the synthesized material has a higher purity. In addition, the hydrothermal reaction controls the crystal morphology and particle size of the final product by adjusting the reaction conditions, and is suitable for the preparation of various forms of nanostructures. Therefore, we use the hydrothermal synthesis method to grow a layer of piezoelectric particles in situ on the metal surface after laser ablation, and we can obtain a uniform and highly adherent piezoelectric nanocoating on the metal surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 This is a SEM image of the titanium plate after laser ablation in Example 1 of the present invention.

[0029] Figure 2 This is a SEM image of the tantalum plate after laser ablation in Example 4 of the present invention.

[0030] Figure 3 This is a SEM image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 1 of the present invention.

[0031] Figure 4 This is a SEM image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 2 of the present invention.

[0032] Figure 5 This is a SEM image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 3 of the present invention.

[0033] Figure 6 This is a SEM image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 4 of the present invention.

[0034] Figure 7 This is a SEM image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 5 of the present invention.

[0035] Figure 8 This is a SEM image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 6 of the present invention.

[0036] Fig. 9 This is a SEM image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 7 of the present invention.

[0037] Fig.10 This is a SEM image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 8 of the present invention.

[0038] Fig.11 This is a SEM image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 9 of the present invention.

[0039] Fig.12 This is an XRD image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 1 of the present invention.

[0040] Fig.13 This is the XRD image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 2 of the present invention.

[0041] Fig.14 This is the XRD image of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 3 of the present invention.

[0042] Fig.15 This is the XRD image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 4 of the present invention.

[0043] Fig.16This is the XRD image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 5 of the present invention.

[0044] Fig.17 This is the XRD image of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Example 6 of the present invention.

[0045] Fig.18 This is an XRD image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 7 of the present invention.

[0046] Fig.19 This is an XRD image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 8 of the present invention.

[0047] Fig. 20 This is an XRD image of the lithium tantalate coating obtained after hydrothermal synthesis of the tantalum plate in Example 9 of the present invention.

[0048] Fig.21 The phase amplitude diagram and surface roughness image of the piezoelectric coating obtained in Example 8 of the present invention.

[0049] Fig. 22 This is an image of the piezoelectric response phase and amplitude curve of the piezoelectric coating obtained in Example 8 of the present invention.

[0050] Fig.23 This is a nano scratch test image of the tantalum substrate of the present invention.

[0051] Fig.24 This is a nano scratch test image of the tantalum oxide nano coating according to Example 8 of the present invention.

[0052] Fig.25 This is a nano scratch test image of the lithium tantalate coating of Example 8 of the present invention.

[0053] Fig.26 This is a bar graph of cell activity cultured with different treatments of the present invention.

[0054] Fig. 27 The SEM image of cells adhering to the tantalum substrate of the present invention.

[0055] Fig.28 This is a SEM image of cell adhesion on the lithium tantalate coating of Example 8 of the present invention.

[0056] Fig.29 This is a SEM image of cell adhesion of the lithium tantalate coating of Example 8 of the present invention under ultrasonic stimulation. DETAILED DESCRIPTION

[0057] In view of the problems of poor bonding between existing implant bones and piezoelectric coatings and low mechanical strength, the present invention proposes a medical metal surface piezoelectric coating and a preparation method thereof. This technology can improve the biocompatibility and mechanical properties of the implant, and utilize the piezoelectric properties of the metal surface piezoelectric coating to promote bone integration of the implant and surrounding tissues, and achieve antibacterial effects by generating active oxygen through the piezoelectric effect.

[0058] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments. It should be noted that the materials used in the present invention are all commonly available on the market.

[0059] Example 1

[0060] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0061] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 min respectively, and finally the plate was dried at 30 ° C for 24 h;

[0062] (2) The pre-treated titanium plate was laser ablated using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 10 ns, and a power density of 0.9 J / cm 2 , frequency is 400Hz, processing area is 6cm 2 , processing time is 100min;

[0063] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0064] (4) A 0.1 mol / L strontium hydroxide solution and a strontium carbonate solution were mixed in a ratio of 1:1 to obtain a mixed solution, and the mixed solution was reacted with the titanium plate after laser ablation at 200° C. and 1 MPa for 24 hours.

[0065] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0066] Example 2

[0067] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0068] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 min respectively, and finally the plate was dried at 40 °C for 12 h;

[0069] (2) The pre-treated titanium plate was laser ablated using a nanosecond pulse laser with a wavelength of 1064 nm, a pulse width of 0.5 ns, and a power density of 0.5 J / cm 2 , frequency is 50Hz, processing area is 6cm 2 , processing time is 150min;

[0070] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 10 min, and finally dried at 50°C for 12 h.

[0071] (4) A 1 mol / L strontium hydroxide solution was reacted with the laser-ablated titanium plate at 100° C. and 5 MPa for 24 h.

[0072] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0073] Example 3

[0074] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0075] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 20 min respectively, and finally the plate was dried at 20 ° C for 24 h;

[0076] (2) Laser ablation of the pretreated titanium plate was performed using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 15 ns, and a power density of 15 J / cm 2 , frequency is 500Hz, processing area is 6cm 2 , the processing time is 60min;

[0077] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0078] (4) A 0.01 mol / L strontium carbonate solution was reacted with the laser-ablated titanium plate at 300° C. and 2 MPa for 24 h.

[0079] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0080] Example 4

[0081] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0082] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in turn, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 min respectively, and finally dried at 30 ° C for 24 h;

[0083] (2) Laser ablation of the pretreated titanium plate was performed using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 10 ns, and a power density of 0.9 J / cm 2 , frequency is 400Hz, processing area is 6cm 2 , processing time is 100min;

[0084] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0085] (4) A 0.1 mol / L barium hydroxide solution and a barium carbonate solution were mixed in a ratio of 1:1 to obtain a mixed solution, and the mixed solution was reacted with the titanium plate after laser ablation at 200° C. and 3 MPa for 24 hours.

[0086] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0087] Example 5

[0088] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0089] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 min respectively, and finally the plate was dried at 40 °C for 12 h;

[0090] (2) The pre-treated titanium plate was laser ablated using a nanosecond pulse laser with a wavelength of 1064 nm, a pulse width of 0.5 ns, and a power density of 0.5 J / cm 2 , frequency is 50Hz, processing area is 6cm 2, processing time is 150min;

[0091] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 10 min, and finally dried at 50°C for 12 h.

[0092] (4) A 1 mol / L barium hydroxide solution was reacted with the laser-ablated titanium plate at 100° C. and 5 MPa for 24 h.

[0093] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0094] Example 6

[0095] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0096] (1) The titanium plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 20 min respectively, and finally the plate was dried at 20 ° C for 24 h;

[0097] (2) Laser ablation of the pretreated titanium plate was performed using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 15 ns, and a power density of 15 J / cm 2 , frequency is 500Hz, processing area is 6cm 2 , the processing time is 60min;

[0098] (3) The titanium plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0099] (4) A 0.01 mol / L barium carbonate solution was reacted with the laser-ablated titanium plate at 300° C. and 1 MPa for 24 h.

[0100] (5) The titanium plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the titanium plate.

[0101] Example 7

[0102] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0103] (1) The tantalum plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in turn, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 minutes respectively, and finally dried at 30°C for 24 hours;

[0104] (2) The pre-treated tantalum plate was laser ablated using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 10 ns, and a power density of 0.9 J / cm 2 , frequency is 400Hz, processing area is 6cm 2 , processing time is 100min;

[0105] (3) The tantalum plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0106] (4) A 0.1 mol / L lithium hydroxide solution and a lithium carbonate solution were mixed in a ratio of 1:1 to obtain a mixed solution, and the mixed solution was reacted with the laser ablated tantalum plate at 200° C. and 4 MPa for 24 hours.

[0107] (5) The tantalum plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the tantalum plate.

[0108] Example 8

[0109] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0110] (1) The tantalum plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in turn, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 minutes respectively, and finally the plate was dried at 40°C for 12 hours;

[0111] (2) The pre-treated tantalum plate was laser ablated using a nanosecond pulse laser with a wavelength of 1064 nm, a pulse width of 0.5 ns, and a power density of 0.5 J / cm 2 , frequency is 50Hz, processing area is 6cm 2 , processing time is 150min;

[0112] (3) The tantalum plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 10 minutes, and finally dried at 50°C for 12 hours.

[0113] (4) A lithium hydroxide solution with a concentration of 1 mol / L is reacted with the laser ablated tantalum plate at 100° C. and 5 MPa for 24 hours.

[0114] (5) The tantalum plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the tantalum plate.

[0115] Example 9

[0116] This embodiment provides a method for preparing a piezoelectric coating on a medical metal surface, and the specific steps are as follows:

[0117] (1) The tantalum plate was polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in turn, and then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 20 minutes respectively, and finally the plate was dried at 20°C for 24 hours;

[0118] (2) The pre-treated tantalum plate was laser ablated using a nanosecond pulse laser with a wavelength of 532 nm, a pulse width of 15 ns, and a power density of 15 J / cm 2 , frequency is 500Hz, processing area is 6cm 2 , the processing time is 60min;

[0119] (3) The tantalum plate after laser ablation was rinsed with pure water and anhydrous ethanol in turn and ultrasonicated for 20 minutes, and finally dried at 30°C for 24 hours.

[0120] (4) A lithium carbonate solution with a concentration of 0.01 mol / L is reacted with the laser-ablated tantalum plate at 300° C. and 1 MPa for 24 hours.

[0121] (5) The tantalum plate after hydrothermal synthesis is rinsed with pure water and anhydrous ethanol in turn and ultrasonically treated for 20 minutes, and finally dried at 30° C. for 24 hours, thereby obtaining a piezoelectric coating on the surface of the tantalum plate.

[0122] Characterization and performance testing of piezoelectric coatings

[0123] The performance and characterization results of the piezoelectric coating obtained in the above examples were tested, and the piezoelectric coating obtained in the examples was subjected to a CCK-8 test and a cell adhesion test.

[0124] The surface morphology of the coating was observed by scanning electron microscopy (SEM, Regulus8100), the physical phase of the surface piezoelectric coating was detected by X-ray diffractometer (XRD, Smartlab SE), the piezoelectric properties of the coating were determined by piezoelectric response force microscopy (PFM, DimensionIcon, Bruker), and the bonding degree and hardness of the surface oxide nanolayer and the piezoelectric coating were determined by a nano scratch tester (Hysitron TI 950).

[0125] The cytotoxicity of the surface nanocoating was determined by the CCK-8 method. The specific steps are as follows:

[0126] Rat bone marrow mesenchymal stem cells (BMSCs) were processed into a cell suspension, and the cell suspension and the sample were added to the cell culture medium together, and cultured at 37°C, 5% CO2 for 1 day, 3 days, and 5 days, and the co-cultured samples were taken out at the corresponding time points. The experiment set up three treatments: the control group: the sample was set as a tantalum substrate and no ultrasound was used during the culture period; the treatment group 1: the sample was set as the piezoelectric coating obtained in Example 8 and no ultrasound was used during the culture period; the treatment group 2: the sample was set as the piezoelectric coating obtained in Example 8 and ultrasound treatment was performed during the culture period, and the ultrasound treatment was performed at 3W / cm 2 Ultrasound at low intensity for 5 minutes, once every two days. Take the cell proliferation fluid, prepare CCK-8 solution according to the ratio of low-glucose culture medium: cell proliferation fluid = 9:1, then move the tantalum substrate and the piezoelectric coating sample material obtained in Example 8 to the blank wells of the 96-well plate, and add 400 microliters of CCK-8 solution to each well. Incubate at 37°C in the dark for 2 hours. After reaching the time point, aspirate 100 microliters of the reaction solution and add it to the 96-well plate, aspirate each well three times as three replicates, and then use a microplate reader to detect the optical density value (OD) at 450nm.

[0127] The adhesion of cells on the sample surface was observed by scanning electron microscopy (SEM, Regulus8100). The cells and materials were cultured at 37°C and 5% CO2 for 3 days, during which the ultrasound group was irradiated at 3W / cm 2 Ultrasound was performed for 5 min at the lowest intensity, and once every two days. The samples were washed three times with PBS and fixed with 4% paraformaldehyde. After being placed at 4°C for 12 hours overnight, the samples were washed three times with PBS again, and gradient dehydration was performed (using 30%, 50%, 70%, 90%, 95% and 100% anhydrous ethanol, respectively, and each gradient reaction lasted for 10 minutes), and finally the samples were dried at 40°C for half an hour in a vacuum drying oven.

[0128] in, Figure 1 and Figure 2 The SEM images of the titanium plate in Example 1 and the tantalum plate in Example 7 after laser ablation are respectively described. As can be seen from the figure, the particle size of the nanoparticles on the metal surface is in the range of 10-50nm, and the particles are evenly distributed.

[0129] Figure 3 , Figure 4 and Figure 5 The SEM images of the strontium titanate coating obtained after hydrothermal synthesis of the titanium plate in Examples 1 to 3 are respectively described. As can be seen from the figure, the particle size of the strontium titanate piezoelectric coating is in the range of 30-100 nm, and the particles are evenly distributed.

[0130] Figure 6 , Figure 7 and Figure 8 The SEM images of the barium titanate coating obtained after hydrothermal synthesis of the titanium plate in Examples 4 to 6 are respectively described. As can be seen from the figure, the particle size of the barium titanate piezoelectric coating is in the range of 10-100 nm, and the particles are evenly distributed.

[0131] Fig. 9 , Fig.10 and Fig.11 , and respectively describe the SEM images of the lithium tantalate coating obtained after the hydrothermal synthesis of the tantalum plate in Examples 7 to 9. As can be seen from the figure, the particle size of the lithium tantalate piezoelectric coating is in the range of 20-100 nm, and the particles are evenly distributed.

[0132] Fig.12 , Fig.13 and Fig.14 The XRD images of the strontium titanate coatings obtained after hydrothermal synthesis of the titanium plates in Examples 1 to 3 are described respectively. As can be seen from the figures, the components of the strontium titanate piezoelectric coatings obtained in Examples 1, 2, and 3 respectively conform to the physical phase of strontium titanate, are consistent with the target components, and the prepared strontium titanate piezoelectric coatings have good crystallinity.

[0133] Fig.15 , Fig.16 and Fig.17 The XRD images of the barium titanate coatings obtained after hydrothermal synthesis of the titanium plates in Examples 4 to 6 are described respectively. As can be seen from the figures, the components of the barium titanate piezoelectric coatings obtained in Examples 4, 5, and 6 respectively conform to the physical phase of barium titanate, and the prepared barium titanate piezoelectric coatings have good crystallinity.

[0134] Fig.18 , Fig.19 and Fig. 20 The XRD images of the lithium tantalate coatings obtained after hydrothermal synthesis of the tantalum plates in Examples 7 to 9 are described respectively. As can be seen from the figures, the components of the lithium tantalate piezoelectric coatings obtained in Examples 7, 8, and 9 respectively conform to the physical phase of lithium tantalate, and the prepared lithium tantalate piezoelectric coatings have good crystallinity.

[0135] Fig.21 The phase amplitude diagram and the surface roughness image of the piezoelectric coating obtained in Example 8 are described. As can be seen from the figure, the lithium tantalate piezoelectric coating obtained in Example 8 has piezoelectric properties and further confirms that the surface particle size is 20-60nm.

[0136] Fig. 22 The image depicts the piezoelectric response phase and amplitude curve of the piezoelectric coating obtained in Example 8. As can be seen from the figure, it is further confirmed that the lithium tantalate piezoelectric coating obtained in Example 8 has piezoelectric properties.

[0137] Fig.23 , Fig.24 , Fig.25 The nano scratch test images of tantalum, tantalum oxide nano coating and lithium tantalate coating obtained in Example 8 are described respectively. As can be seen from the figure, the critical load of tantalum surface is about 4571.4 μN (such as Figure 1 After laser ablation, the critical load of the generated oxide nanocoating was increased to 9204.9 μN (e.g. Fig. 22 ), significantly improving the mechanical strength of the material surface, and indicating that the oxide nano-coating has a high degree of bonding. The critical load of the lithium tantalate coating generated in situ on the material surface by hydrothermal reaction is about 7664.0μN (such as Fig.23 ), although the bonding degree is reduced compared to the oxide nano coating, the coating still has a high bonding degree and mechanical strength relative to the tantalum surface.

[0138] Fig.26 The cell activity bar graph of CCK-8 experiment with different materials is described. As can be seen from the figure, the ultrasonically treated and non-ultrasonicated lithium tantalate coating groups have good cell activity on days 1, 3, and 5, and the cell activity is similar to that of the tantalum matrix treatment group, while the cell activity of the ultrasonically treated lithium tantalate coating group is improved on the 5th day, indicating that the piezoelectric coating is non-cytotoxic, the piezoelectric coating has good cell compatibility, and the piezoelectric coating is more conducive to cell growth under ultrasonic stimulation.

[0139] Fig. 27 , 28 29 respectively describe SEM images of tantalum, the lithium tantalate coating obtained from Example 8, and the cell adhesion of the lithium tantalate coating under ultrasound stimulation. As can be seen from the figure, the cells on the surface of the lithium tantalate coating have better spreading and more pseudopodia than those on tantalum, and the cells spread more under ultrasound stimulation.

[0140] As can be seen from the above, the metal material is not deformed or damaged after laser ablation in the embodiment of the present invention, and the precision is high. The metal surface after laser ablation of the piezoelectric coating on the metal surface has strong mechanical strength, and the piezoelectric coating is evenly attached to the metal surface with strong adhesion. The piezoelectric coating has good biocompatibility, and the surface nanostructure is conducive to cell attachment. After ultrasonic stimulation, the biocompatibility and the spreading of the material surface are improved.

[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a piezoelectric coating on a medical metal surface, characterized in that: include: Surface laser ablation of metals to obtain oxidized nano-coatings; The alkaline solution and the oxidized nano-coating are subjected to a hydrothermal reaction under high temperature and high pressure conditions to obtain a piezoelectric coating; Wherein, the metal is tantalum, titanium or niobium; the high temperature and high pressure conditions are 100-300°C and 1-5MPa.

2. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The metal is pretreated before laser ablation; preferably, the metal is polished with sandpaper, then cleaned with an organic solvent and pure water in sequence, and finally dried at 20-40°C; further preferably, the medical metal is polished with 400 mesh, 600 mesh, 1000 mesh and 1200 mesh sandpaper in sequence, then ultrasonically cleaned with acetone, anhydrous ethanol and pure water for 30 minutes in sequence, and dried at 25-35°C for 12-24 hours.

3. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: Laser ablation is performed in air.

4. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The laser ablation is laser surface direct writing ablation; preferably, it is performed using a pulsed laser; further preferably, the wavelength of the pulsed laser is 532-1064nm, the pulse width is 0.5-15ns, and the power density is 0.5-15.0J / cm 2 , frequency is 50-500Hz.

5. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The metal after laser ablation is cleaned and dried before undergoing hydrothermal reaction; preferably, the metal after laser ablation is cleaned and dried, and the preferred method is: rinse with pure water and anhydrous ethanol respectively and ultrasonicate for 10-30 minutes, and finally dry at 30-50°C for 12-24 hours.

6. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The alkaline solution is one or both of strontium hydroxide and strontium carbonate; preferably, it is a mixed solution of strontium hydroxide and strontium carbonate. More preferably, the concentration of strontium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of strontium carbonate is 0.01-1 mol / L.

7. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The alkaline solution is one or both of barium hydroxide and barium carbonate; preferably, it is a mixed solution of barium hydroxide and barium carbonate. More preferably, the concentration of barium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of barium carbonate is 0.01-1 mol / L.

8. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: The alkaline solution is one or both of lithium hydroxide and lithium carbonate; preferably, it is a mixed solution of lithium hydroxide and lithium carbonate. More preferably, the concentration of lithium hydroxide in the alkaline solution is 0.01-1 mol / L; the concentration of lithium carbonate is 0.01-1 mol / L.

9. The method for preparing a medical metal surface piezoelectric coating according to claim 1, characterized in that: After the hydrothermal reaction, the metal is cleaned and dried; preferably, the method is to rinse with pure water and anhydrous ethanol respectively and ultrasonicate for 10-20 minutes, and finally dry at 30-50°C for 12-24 hours.

10. A medical metal surface piezoelectric coating, characterized in that: Obtained by the preparation method as claimed in claims 1-9; preferably, the particle size of the piezoelectric coating on the metal surface is 10-100nm.

Citation Information

Patent Citations

  • Method for quickly preparing oxide multi-stage nanostructure

    CN106624369A

  • Ultraviolet detector based on zinc stannate / graphene composite material and preparation method thereof

    CN111276565A

  • Preparation method of biological piezoelectric coating on surface of titanium-based material

    CN113445102A

  • Preparation method for biological piezoelectric antibacterial coating on surface of medical titanium alloy

    CN113502524A